2022
DOI: 10.1111/mec.16568
|View full text |Cite
|
Sign up to set email alerts
|

Seq’ and ARMS shall find: DNA (meta)barcoding of Autonomous Reef Monitoring Structures across the tree of life uncovers hidden cryptobiome of tropical urban coral reefs

Abstract: Coral reefs are among the richest marine ecosystems on Earth, but there remains much diversity hidden within cavities of complex reef structures awaiting discovery. While the abundance of corals and other macroinvertebrates are known to influence the diversity of other reef‐associated organisms, much remains unknown on the drivers of cryptobenthic diversity. A combination of standardized sampling with 12 units of the Autonomous Reef Monitoring Structure (ARMS) and high‐throughput sequencing was utilized to unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 116 publications
2
14
0
Order By: Relevance
“…How predators respond to enhanced resource availability along this trajectory could be addressed using extended size spectra analyses (Heather et al, 2021) from cryptobenthic predators (Mihalitsis et al, 2022) to large higher order predators beyond the benthos. The knowledge gained here would benefit from the increased taxonomic resolution of sessile taxa and motile cryptofauna. There are extreme taxonomic constraints in the cryptofauna, yet molecular and environmental DNA metabarcoding techniques are growing in popularity to partition cryptic community structures (Carvalho et al, 2019; Ip et al, 2022; Leray & Knowlton, 2015; Pearman et al, 2018; Plaisance et al, 2009). These approaches seem important to employ in the context of the ecological outcomes presented from microhabitat to seascape here. The intermediate disturbance hypothesis (Connell, 1978; Dial & Roughgarden, 1998) may help to explain the nonstructured seascape patterns in the cover of sessile taxa and motile cryptofauna density observed here, which were greatest in the mid‐exposure site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How predators respond to enhanced resource availability along this trajectory could be addressed using extended size spectra analyses (Heather et al, 2021) from cryptobenthic predators (Mihalitsis et al, 2022) to large higher order predators beyond the benthos. The knowledge gained here would benefit from the increased taxonomic resolution of sessile taxa and motile cryptofauna. There are extreme taxonomic constraints in the cryptofauna, yet molecular and environmental DNA metabarcoding techniques are growing in popularity to partition cryptic community structures (Carvalho et al, 2019; Ip et al, 2022; Leray & Knowlton, 2015; Pearman et al, 2018; Plaisance et al, 2009). These approaches seem important to employ in the context of the ecological outcomes presented from microhabitat to seascape here. The intermediate disturbance hypothesis (Connell, 1978; Dial & Roughgarden, 1998) may help to explain the nonstructured seascape patterns in the cover of sessile taxa and motile cryptofauna density observed here, which were greatest in the mid‐exposure site.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge gained here would benefit from the increased taxonomic resolution of sessile taxa and motile cryptofauna. There are extreme taxonomic constraints in the cryptofauna, yet molecular and environmental DNA metabarcoding techniques are growing in popularity to partition cryptic community structures (Carvalho et al, 2019;Ip et al, 2022;Leray & Knowlton, 2015;Pearman et al, 2018;Plaisance et al, 2009). These approaches seem important to employ in the context of the ecological outcomes presented from microhabitat to seascape here.…”
Section: Conclusion and Hypothesesmentioning
confidence: 99%
“…In this case, diversity measures could thus not be used as a proxy for ecological importance. Finally, Ip, Chang, Oh, et al (2022) combine standardised sampling using Autonomous Reef Monitoring Structures (ARMS) and high-throughput sequencing to test whether coral cover shapes diversity patterns among organisms inhabiting hidden spaces within the reef matrix (the "cryptobiome"). They showed that, while marine fungi, bacteria, phytoplankton and other planktonic organisms were impacted primarily by abiotic factors (depth, temperature, level of particles in the water column and distance from the mainland), diversity patterns in larger-sized metazoans were associated with coral cover.…”
Section: Community Assembly Processesmentioning
confidence: 99%
“…Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes ‘papers that highlight the power of high‐throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary ‐omics data types and/or models/theory to infer overall ecosystem processes’ (Gillespie et al., 2023). The impressive collection of 44 manuscripts covers a wide range of topics: community assembly processes (Andujar et al., 2022; Arjona et al., 2022; Emerson et al., 2022; Govender et al., 2022; Guerrieri et al., 2022; Ip, Chang, Oh, et al., 2022; Kiemel et al., 2022; Li et al., 2022; Macheriotou et al., 2023; Menéndez‐Serra et al., 2023; Nappi et al., 2022; Noguerales et al., 2023; Overcast et al., 2023; Pino et al., 2023; Van der Loos et al., 2022; Wang et al., 2022), interaction networks (Ando et al., 2022; Bell et al., 2022; Dürrbaum et al., 2022; Encinas‐Viso et al., 2022; Ficetola & Taberlet, 2023; Graham et al., 2022; Ip, Chang, Tun, et al., 2022; Lowe et al., 2022; Lu et al., 2022; Lue et al., 2022; Pitteloud et al., 2022; Srivathsan et al., 2022; Tommasi et al., 2022), cross‐scale interactions and microbiomes (Brinker et al., 2022; Câmara dos Reis et al., 2022; Hu et al., 2022; Kivistik et al., 2022; Manthey et al., 2022; Merges et al., 2022; Michel et al., 2022; Molina et al., 2022; Navine et al., 2022; Pereira et al., 2022; Perez‐Lamarque & Morlon, 2022; Rolshausen et al., 2022), and invasive species/homogenization (Andrés et al., 2023; Graham et al., 2022; Hampel et al., 2022; Kennedy et al., 2022; Overcast et al., …”
Section: Highlights Of 2023mentioning
confidence: 99%
“…Collectively the articles in this Special Issue 'underline the huge impact of the anthropogenic environment in microbial evolution, including the emergence and spread of pathogens as well as the benefits provided by domesticated or mutualistic fungi and bacteria'(Giraud et al, 2023).Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes 'papers that highlight the power of high-throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary -omics data types and/or models/theory to infer overall ecosystem processes'(Gillespie et al, 2023). The impressive collection of 44 manuscripts covers a wide range of topics: community assembly processes(Andujar et al, 2022;Arjona et al, 2022;Emerson et al, 2022;Govender et al, 2022;Guerrieri et al, 2022;Ip, Chang, Oh, et al, 2022;Kiemel et al, 2022;Li et al, 2022;Macheriotou et al, 2023;Menéndez-Serra et al, 2023;Nappi et al, 2022;Noguerales et al, 2023;Overcast et al, 2023;Pino et al, 2023;Van der Loos et al, 2022;Wang et al, 2022), interaction networks(Ando et al, 2022;Bell et al, 2022;Dürrbaum et al, 2022;Encinas-Viso et al, 2022;Ficetola & Taberlet, 2023;Graham et al, 2022;Ip, Chang, Tun, et al, 2022;Lowe et al, 2022;Lu et al, 2022;Lue et al, 2022;Pitteloud et al, 2022;Srivathsan et al, 2022;Tommasi et al, 2022), cross-scale interactions and microbiomes(Brinker et al, 2022;Câmara dos Reis et al, 2022...…”
mentioning
confidence: 99%